An experimental study on the humour effect and mood-congruent memory among IIUM students - Tunku Saraa-Zawyah Tunku Badli (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
The aims of the present study are threefold. Firstly, to determine whether individuals in either a neutral mood or a dysphoric mood recall more words from humorous or non-humorous video clips. Secondly, to determine whether dysphoric individuals recall fewer words overall than individuals in a neutral mood, and lastly, to determine whether the effect of humour on memory recall is due to humour per se or the experience of positive affect produced by it. A two-factor mixed factorial design was employed in an attempt to fulfil the aims of the study. Each of the two independent variables was manipulated on two levels. The first was the mood of the participants who were either neutral or dysphoric. The second variable was video type, which were humorous and non-humorous. Both groups viewed the two video types which included displayed words and were asked to recall as many words from the videos; thus the number of words recalled was the dependent variable. The two hypotheses put forward were supported. The first is that, consistent with mood-congruent memory theory, dysphoric individuals recalled fewer words from the humorous videos compared to individuals in a neutral mood. The second is that the number of words recalled from the humorous video clips will be greater than the number of words recalled from the non-humorous video clips.